Auditoría administrativa a la corporación Cofispi cantón Pichincha. Periodo 2012 - Moyano Vergara, Mariuxi Angélica (2015)
An administrative audit is the total or partial analytic revision of an organization with the purpose of to know its acting level and to profile opportunities of improvement to innovate value and to create a sustainable competitive advantage. The administrative audit formulates and it presents an opinion on the administrative, managerial and operative aspects, putting emphasis in the grade of effectively and efficiency with which the material and financial resources have been used by means of modification of political, operative controls and work, it develops the ability to identify the later operational causes and they explain evident adverse symptoms in the efficient administration. The objective of the administrative audit is to improve the operative methods and to increase the yield with constructive ends and of support to the examined necessities. The administrative audit determines if the function or activity lower exam it could operate in a more efficient, economic and effective way. In this applied audit to the Corporation COFISPI, you could determine that the company maintains a plan of strategic development that allows to determine the institutional objectives in a clear and defined way; during the evaluation to the internal check could be detected a series of discoveries that you/they understand the structure of control of the valued organization, like part from the evaluation to the administrative processes and the internal check they were carried out the calculations corresponding to inherent risks, control risk and detection risk, what took us to establish 2,13% of audit risk. Finally, the discoveries and administrative procedures that involve the weaknesses that were presented in the Corporation COFISPI during the valued period are exposed respectively in the internal check report and the final report of audit.